An exploratory study of visually impaired students' perceptions of inclusive mathematics education - AYDIN, EMİN (SAGE PUBLICATIONS LTD, 2015)
The Turkish Disability Act introduced inclusive education to Turkey as a solution to the problems experienced by students with disabilities, including visually impaired students. The main purpose of this study was to explore the challenges faced by visually impaired students learning high school mathematics in inclusive classrooms in Turkey. The data were qualitative, consisting of interviews conducted with three high school graduates; they were analysed using the constant comparison method. In the interviews, students described the effects of various teaching methods on their learning and evaluated the social aspect (broadly speaking) of inclusive education. The results show that while the social needs of visually impaired Turkish students were adequately met through inclusive education, their academic needs were not, which we speculate to be partly because of mathematics teachers' negative attitudes towards inclusive education.
Keywords: Education in Turkey; inclusive education; mathematics education; social aspect of learning; visually impaired students